Mindful Learning Experience Facilitates Mastery Experience Through Heightened Flow and Self-Efficacy in Game-Based Creativity Learning - Yeh, Yu-chu; Chen, Szu-Yu; Rega, Elisa Marie; Lin, Chin-Shan (Frontiers in Psychology, 2019)
This study was performed within the limited framework of computer-game-based educational programs designed to enhance creativity. Furthermore, the utilization of mindful learning and moderators such as flow, mastery experience, and self-efficacy, brings this research to the forefront of modern educational practices. The present researchers developed a comprehensive game-based creativity learning program for fifth and sixth grade pupils. Further analyses presented relationship trends between mindful learning experience, flow experience, self-efficacy, and mastery experience. Eighty-three 5th and 6th grade participants undertook the six-week game-based creativity learning program. Upon completion of the experimental instruction, self-evaluation revealed that participants with higher scores on the concerned variables improved more in both creative ability and confidence than their counterparts. Additionally, path model analysis revealed that mindful learning experience was a powerful predictor of both mastery experience and flow experience; it also influenced mastery experience through flow experience and self-efficacy. The findings support the effectiveness of the game-based learning program developed in this study. Moreover, this study contributes to the theoretical construction of how game-based learning can be designed to facilitate mindful learning experience, flow experience, self-efficacy, and mastery experience during creativity. Some additional enhancement mechanisms utilized in the program were: rewards for high-quality performance, challenging tasks, a variety of design components, immediate feedback, and idea sharing. The theoretical design of this study provides support for the ongoing scientific investigation of new applications of mindful learning in educational programs concerning the learning of creativity.